2018
DOI: 10.1016/j.envpol.2017.11.096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the relationship between temporal changes in land use and resulting water quality

Abstract: Changes in land use have a direct impact on receiving water quality. Effective mitigation strategies require the accurate prediction of water quality in order to enhance community well-being and ecosystem health. The research study employed Bayesian Network modelling to investigate the validity of using cross-sectional and longitudinal data on water quality and land use for predicting water quality in a mixed use catchment and the role it plays in the generation of blue-green algae in the receiving marine envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 19 publications
2
29
0
2
Order By: Relevance
“…It is worth noting that the various linkages between LULC and surface water quality and the resultant influences on the transmission of infectious diseases were identified; however, the studies focused entirely on the negative aspects of land-use change. The potential positive influences of LUC on water quality and disease ecology was found missing in the literature [21,53,54,56,59]. This indicates a potential direction for future research investigations to explore the positive influences of LUC on water quality at different scales in relation to WRID ecology [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that the various linkages between LULC and surface water quality and the resultant influences on the transmission of infectious diseases were identified; however, the studies focused entirely on the negative aspects of land-use change. The potential positive influences of LUC on water quality and disease ecology was found missing in the literature [21,53,54,56,59]. This indicates a potential direction for future research investigations to explore the positive influences of LUC on water quality at different scales in relation to WRID ecology [7].…”
Section: Discussionmentioning
confidence: 99%
“…On average, it was observed that a higher number of the included studies were countries classified as developing regions, such as sub-Saharan Africa, Asia, and Latin America, where there is limited potable drinking-water, poor wastes management, poor water quality monitoring, unsustainable agricultural practices, and limited access to funds for scientific research. There are many studies on water quality and diseases; however, these studies lacked explicit linkages to WRID [53,54].…”
Section: Distribution Of Studies By Country/regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies focus on the spatial effects of human activities on water quality, and the effects of landscape pattern and structure of land use in adjacent water bodies or of the reservoirs on water quality are studied [23][24][25]. Extensive studies highlight the impacts of different land use types on water quality, such as areal proportion [26,27], topographic characteristics [28][29][30], multi-spatial scales [31,32], and seasonal and temporal changes [33,34]. However, some scholars argued that even with similar or same land use types and proportions, different land use intensities may result in a wide range of water quality [35,36]; only using the quantitative proportion of land use in the watershed to explain the water quality performance will often lead to different findings [10][11][12][13]37,38].…”
Section: Introductionmentioning
confidence: 99%
“…When Filth is thrown in water the toxins travel from the water and when the animals drink that water they get contaminated and when humans tend to eat the meat of the animals is infected by toxins it causes further damage to the humans. Infectious diseases such as cholera and typhoid can be contracted from drinking contaminated water [2]. These may include organic and inorganic substances.…”
mentioning
confidence: 99%